Penanaman Nilai Agama Dalam Membentuk Etika dan Moral - Rizqi, Fatimah Tur; Nadirah, Yahdinil Firda; Sayehu, Sayehu; Fauzi, Anis; Mastoah, Imas; Wasehudin, Wasehudin; Hilmiyati, Fitri (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the internalization of religious values in shaping individuals' ethics and morals, particularly within the context of education. In the era of globalization and rapid technological advancement, there has been a shift in values that affects the behavior of the younger generation. Therefore, the cultivation of religious values becomes a crucial foundation in building ethical and moral character. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that the consistent implementation of religious values through teaching, role modeling, and habituation effectively fosters discipline, responsibility, and positive social behavior. Furthermore, the roles of teachers, family, and environment significantly influence the success of the value internalization process. Thus, the cultivation of religious values is not only cognitive but also encompasses affective and psychomotor aspects integrated into daily life. This study is expected to contribute to the development of educational strategies oriented toward noble character building.